Mutation of SlSBPASE Aggravates Chilling-Induced Oxidative Stress by Impairing Glutathione Biosynthesis and Suppressing Ascorbate-Glutathione Recycling in Tomato Plants - Wang, Meiling; Ding, Fei; Zhang, Shuoxin (Frontiers in Plant Science, 2020)
Sedoheptulose-1,7-bisphosphatase (SBPase) is a crucial enzyme for photosynthetic carbon assimilation in the Calvin-Benson cycle. Previous studies have shown that overexpression of SBPase is advantageous to chilling tolerance in plants; however, the mechanisms of SBPase acting in the improvement of chilling tolerance remain largely unknown. In the present study, we aimed to uncover the essential role of SBPase in the response of tomato plants to oxidative stress induced by low temperature. To fulfill that, we performed an array of comparative studies between slsbpase mutant plants that we previously generated using CRISPR/Cas9 genome editing system and their wild-type counterparts under chilling stress. It was observed that following a 24-h chilling treatment, slsbpase mutant plants accumulated higher levels of reactive oxygen species (ROS) than wild-type plants and consequently, more severe lipid peroxidation occurred in slsbpase plants. Activity assay of antioxidant enzymes showed that mutation in SlSBPASE significantly decreased activities of POD and APX, but surprisingly did not significantly alter activities of SOD and CAT under the chilling condition. Notably, mutation in SlSBPASE reduced the contents of total ascorbate and total glutathione, and suppressed the recycling of AsA and GSH in chilling-stressed tomato plants. In addition, activities of two glutathione biosynthetic enzymes (gamma-glutamylcysteine synthetase and glutathione synthetase) and transcript abundance of their coding genes (GSH1 and GSH2) were markedly reduced in slsbpase mutant plants in comparison with those in wild-type plants under chilling stress. Furthermore, exogenous GSH remarkably mitigated chilling damage in slsbpase plants. Collectively, these results support that mutation in SlSBPASE aggravates chilling-induced oxidative stress by suppressing glutathione biosynthesis and AsA-GSH recycling and suggest that SBPase is required for optimal response to chilling stress in tomato plants. The findings also shed light on the idea to mitigate chilling-induced damages by genetically manipulating a photosynthetic enzyme in plants.